HUBUNGAN DUKUNGAN KELUARGA DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIS YANG MENJALANI TERAPI HEMODIALISA DI RSUD DOK II JAYAPURA - Situmorang, Hotnida Erlin (Magister Pendidikan IPA, UNCEN, 2015)
This study is a correlational study aimed to assess the relationship with the family support quality of life of patients with chronic renal failure undergoing hemodialysis therapy in hospitals Dok II Jayapura. The study population was all patients with chronic renal failure on hemodialysis space consisting of 35 sample technique used is the technique of saturated samples. Data collection is done by distributing questionnaires to all respondents. Data were analyzed using statistical techniques correlation test with the help of SPSS 16.0 application. The results showed that there was a significant relationship between family support with the quality of life of patients with chronic renal failure with a significance level Î± = 5%. The relationship is included in the high category and the direction indicated by coefficient R = 0.784. Keywords: family support, quality of life, chronic renal failure, hemodialysis therapy.